Предмет: Алгебра,
автор: Крис200017
Упростите выражение (3+а)в квадрате - (а-4) в квадрате . При а= - 3/2
Ответы
Автор ответа:
0
( 3 + а ) ^2 - ( а - 4 ) ^2 = 9 + 6а + а^2 - ( а^2 - 8а + 16 ) = 9 + 6а + а^2 - а^2 +8а - 16 = 14а - 7 ;
При а = - 3/2 ;
14а - 7 =7 * ( 2а - 1 ) ;
7 * ( 2 * ( - 3/2 ) - 1 ) = 7 * ( - 3 - 1 ) = 7 * ( - 4 ) = - 28
Похожие вопросы
Предмет: Математика,
автор: artemkolmakovvv
Предмет: Окружающий мир,
автор: dimgareevic546
Предмет: Геометрия,
автор: konstantynrodchenkov
Предмет: Математика,
автор: Наняyf
Предмет: Алгебра,
автор: twerk1baby